Evolução tecnológica dos materiais e geometria de pistões para motores de combustão interna e um estudo de caso de pistão para aplicação em motor diesel com trinca no cubo - Yamawaki, Marcio (2013)
Pistons are one of the most challenged components on an internal combustion engine. The range of thermal and mechanical loads on these components reach limit levels where the applied materials cannot react and are not able to go back to its original condition. We can say that pistons are the fuses of an internal combustion engine. The adequate selection of materials for the pistons must take in account the usage of the engines. For passenger cars for instance, typically light alloys are chosen in order to attend the low fuel consumption and emission level demands. For commercial vehicles there are more freedom choosing the materials because weight does not play the same level of role but on the other hand requires materials that can resist the very high loads involved. The objective of this work is to describe the criteria s involved on a piston design and how closed they are connected with the adequate material selection. A case study of a aluminum piston for Diesel engine application that presented a pin bore crack related to feathery grain formation will be shown.